A novel homozygous ARL13B variant in patients with Joubert syndrome impairs its guanine nucleotide-exchange factor activity. (December 2017) - Rafiullah, Rafiullah; Long, Alyssa; Ivanova, Anna; Ali, Hazrat; Berkel, Simone; Mustafa, Ghulam; Paramasivam, Nagarajan; Schlesner, Matthias; Wiemann, Stefan; Wade, Rebecca; Bolthauser, Eugen; Blum, Martin; et al.
Abstract ARL13B encodes for the ADP-ribosylation factor-like 13B GTPase, which is required for normal cilia structure and Sonic hedgehog (Shh) signaling. Disruptions in cilia structure or function lead to a class of human disorders called ciliopathies. Joubert syndrome is characterized by a wide spectrum of symptoms, including a variable degree of intellectual disability, ataxia, and ocular abnormalities. Here we report a novel homozygous missense variant c.[223G>A] (p.(Gly75Arg) in theARL13B gene, which was identified by whole-exome sequencing of a trio from a consanguineous family with multiple-affected individuals suffering from intellectual disability, ataxia, ocular defects, and epilepsy. The same variant was also identified in a second family. We saw a striking difference in the severity of ataxia between affected male and female individuals in both families. Both ARL13B and ARL13B-c.[223G>A] (p.(Gly75Arg) expression rescued the cilia length and Shh defects displayed byArl13b hennin (null) cells, indicating that the variant did not disrupt either ARL13B function. In contrast, ARL13B-c.[223G>A] (p.(Gly75Arg) displayed a marked loss of ARL3 guanine nucleotide-exchange factor activity, with retention of its GTPase activities, highlighting the correlation between its loss of function as an ARL3 guanine nucleotide-exchange factor and Joubert syndrome.